Handbook of microwave component measurements : with advanced VNA techniques - Dunsmore, Joel P. (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2012)
"A practical guide to the most modern techniques for microwave measurements Handbook of Microwave Component Measurements is a complete reference to this topic, focusing on the modern measurement tools, such as a Vector Network Analyzer (VNA), gathering in one place all the concepts, formulas, and best practices of measurement science. It includes basic concepts in each chapter as well as appendices which provide all the detail needed to understand the science behind microwave measurements. The book offers an insight into the best practices for ascertaining the true nature of the device-under-test (DUT), optimizing the time to setup and measure, and to the greatest extent possible, remove the effects of the measuring equipment from that result. Furthermore, the author presents information in a way that is easily accessible to the student or new engineer, but complete enough to provide details of measurement science for even the most advanced applications and researchers. Explains the interactions between the device-under-test (DUT) and the measuring equipment by demonstrating the best practices for ascertaining the true nature of the DUT, and optimizing the time to set up and measure Offers a detailed explanation of algorithms and mathematics behind measurements and error correction Provides numerous illustrations (e.g. block-diagrams for circuit connections and measurement setups) and practical examples on real-world devices, which can provide immediate benefit to the reader Written by the principle developer and designer of many of the measurement methods described Includes an accompanying website containing example test scripts for setting up and processing device measurement and data "--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Microwave devices -- Testing; Microwave devices -- Testing; TECHNOLOGY & ENGINEERING -- Microwaves; Microwave devices -- Testing; Microwave devices / Testing; Electronic books; Electronic books